ANALISIS PERENCANAAN ANGGARAN BERBASIS KINERJA DI KANTOR SATUAN POLISI PAMONG PRAJA KOTA PEMATANGSIANTAR - Viki Zuliansyah (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2012)
This research aims to determine how performance-based budget planning is implemented in the Civil Service Police Force Pematangsiantar city and to find out the constraints faced and to know the efforts should be done. This researchuses descriptive qualitative approach using data collection techniques participant observation, in-depth interviews and documentary studies. There are 12 key information in this research. To test credibility of data , it uses three methodsnamely the extension of the observation, improvement and triangulation of data triangulation and theory triangulation. The results shows that in budget planning the Civil Service Police Force Pematangsiantar city still has not appliedperformance-based budgeting. The research find few obstacles encountered in implementing performance-based budgeting in the office of the Civil Service Police Force Pematangsiantar city, including: 1. The low competence of Human Resources; 2. There are not any performance indicators; 3. Lack of Internal coordination; 4. The limited budget allocated; 5. Lack of coordination with making up teams budget in the Pematangsiantar City Government and the Parliament Pematangsiantar City.